Actinic lichen planus in a child - a rare entity - Neerja Puri (Our Dermatology Online, 2014)
Lichen Planus actinicus (LP actinicus) is a variant of lichen planus often confined to individuals in tropical and subtropical regions. The lesions involve sun-exposed areas and are characterized by well-defined nummular patches which have a deeply hyperpigmented centre surrounded by a hypopigmented zone. It mainly involves teenagers with an Asian racial profile. We report a rare case of a 10 year old male child who reported to the department of dermatology with multiple annular pigmented patches on the face, forearms and shins which developed slowly over a period of one year.